ANALYSIS OF WAGE DISTRIBUTION AMONG FACTORY WORKERS BOTTLED DRINKING WATER ACCORDING TO IJÂRAH’ ALA AL-'AMÂL CONTRACT: A Study at the Tera Factory in Seulimeum District - Muhammad Rizki; Muhammad Iqbal (Al-Mudharabah: Jurnal Ekonomi dan Keuangan Syariah, 2026)
Sistem pengupahan merupakan aspek penting dalam hubungan kerja yang berpengaruh langsung terhadap keadilan dan kesejThe wage system is an important aspect of labour relations that directly affects workers’ fairness and welfare. From an Islamic law perspective, wages are regulated through the ijârah ‘ala al-‘amâl contract, which emphasises clarity, fairness, and the protection of the rights and obligations of the parties. However, in practice, there are still differences in treatment and potential injustices in the wage system, particularly between daily and monthly workers. The main issue in this study lies in the mechanism of wage distribution for workers at the Tera Bottled Water Factory in Seulimeum District and the extent to which it complies with the principle of fairness in the ijârah ‘ala al-‘amâl contract. The research method is descriptive, analytical, and qualitative, with an empirical sociological approach, and is conducted through a literature review, in-depth interviews with workers, and field observations. The results show that daily workers do not receive wages when they do not work due to factory operational disruptions not caused by their negligence. In contrast, monthly workers still receive their basic wages. This practice has the potential to burden daily workers with operational risks and does not fully reflect the principle of fairness in the ijârah ‘ala al-‘amâl contract. Therefore, it is necessary to review the wage policy to make it more equitable and in line with Sharia values in employment relationshipsahteraan pekerja. Dalam perspektif hukum Islam, pengupahan diatur melalui akad ijârah ‘ala al-‘amâl yang menekankan kejelasan, keadilan, serta perlindungan hak dan kewajiban para pihak. Namun, dalam praktiknya masih ditemukan perbedaan perlakuan dan potensi ketidakadilan dalam sistem pengupahan, khususnya antara pekerja harian dan pekerja bulanan. Permasalahan utama dalam penelitian ini terletak pada mekanisme pembagian upah pekerja di Pabrik Air Minum Dalam Kemasan Tera Kecamatan Seulimeum serta sejauh mana kesesuaiannya dengan prinsip keadilan dalam akad ijârah ‘ala al-‘amâl. Metode penelitian yang digunakan adalah penelitian kualitatif deskriptif analitis dengan pendekatan sosiologis empiris, yang dilakukan melalui studi kepustakaan, wawancara mendalam dengan pekerja dan observasi lapangan. Hasil penelitian menunjukkan bahwa pekerja harian tidak memperoleh upah ketika tidak bekerja akibat gangguan operasional pabrik yang bukan disebabkan oleh kelalaian mereka, sementara pekerja bulanan tetap menerima upah pokok. Praktik ini berpotensi membebankan risiko operasional kepada pekerja harian dan belum sepenuhnya mencerminkan prinsip keadilan dalam akad ijârah ‘ala al-‘amâl. Oleh karena itu, diperlukan peninjauan ulang kebijakan pengupahan agar lebih berkeadilan dan selaras dengan nilai-nilai syariah dalam hubungan kerja.